Model Pembelajaran Course Review Horay untuk Meningkatkan Pemahaman Konsep Bilangan 1-10 - Darajat Rangkuti; Darmina Eka Sari Rangkuti (Aṭfāluna: Journal of Islamic Early Childhood Education, 2019)
This experimental study aims to increase children’s comprehension of the concepts of number 1-10 by implementing the Course Review Horay Learning Model. The research subjects were group A children in PAUD Tunas Harapan Medan. The understanding of number concepts was evaluated from pretest and posttest with the indicator is to comprehend the concept of number. The scores were analyzed statistically by using the paired-sample t-test. The students in the experimental class were taught by using the Course Review Horay Learning Model, while the control was taught conventionally. The results of the study show the experimental class data group differs from the form control class with a significant value is 0.86 (p = 0.05). The results of the study concluded that the Course Review Horray Learning Model can significantly improve children's ability to understand the concept of number 1-10.